Aplicación de contabilidad de servicio para el transporte del señor Villavicencio Iñiguez Diego Alfredo de la ciudad de Loja, período julio – septiembre 2013 - Tinoco Andrade, Estefanía del Cisne (2016)
This so-called thesis work; "Application of accounting of services for transporting the Lord VILLAVICENCIO IÑIGUEZ DIEGO ALFREDO from the city of LOJA, period July - September 2013" was designed with the aim of developing the practical application of the accounting system suitable for this service company, whose activity to date does not have a specialized advisory, in accordance with the rules and techniques of application of an accounting organization, adjusted to the rules and legal laws. It was also in consideration of the regulation of academic of the University national regime of Loja, prior to choose the degree of engineer in accounting and auditing, CPA. The objectives of the development of the thesis, were reached to make the accounting process that starts with the determination of the initial inventory, Development Plan and Manual of accounts and finally developed the accounting process by applying accounting services, taking into consideration the internal documents such as: role of payments, Assistant sales and purchases and depreciation of property Plant and equipment; It was then determined the State of initial situation; then with the registration of transactions in the journal book; the respective ledgers, Balance checking and worksheet that allowed to obtain financial statements generated. At the conclusion of the work, it has a service accounting system adapted to this transport company, with books of original entry, ledgers and financial statements; It is recommended that you continue running accounting services to the owner of the company can count with economic and financial information in a timely and reliable manner that facilitates decision-making.